A Proposed Model of Halal Insurance Policy Scheme - Gherfal, Fawzi (International Journal of Islamic Economics and Governance, 2023)
It is a well-known fact that Muslim scholars have declared commercial insurance in modern times religiously prohibited (Harm), mainly for the reason that it contains riba (insurance), gharar (misleading), and maysir (gambling or speculation). The Islamic Figh Academy declared the same because it causes a major element of risk, which voids the insurance contract; therefore, it is prohibited. Takaful insurance, a Shariah-compliant insurance, was introduced to replace commercial insurance by eliminating the prohibited elements in commercial insurance. While successfully introduced, Takaful still did not fulfill Shariah's purpose in preventing the injustice practiced, including profiting out of the agony of others. The author introduces a new Islamic insurance (FAWZ) to eliminate the elements of prohibiting commercial insurance while still fulfilling the purpose of Shariah (Maqasid al-Shariah). FAWZ-Insurance is based on a partnership model between the two parties, the insured and the insurer, a model or a transaction called for by Shariah as manifested in Surat Anissa, Verse 29, declaring that Tijara (commerce) is the only permissible transaction amongst believers, whereas Musharakha (partnership) is a form of commerce that is used.